Forma e Conteúdo no Sistema das Artes de Hegel (Revista Eletrônica Estudos Hegelianos, 2021)
The dialectical structure that permeates Hegel’s understanding of the artistic phenomenon in the Lectures on Aesthetics allows him an original apprehension of the individual arts and their relationships with each other, because, unlike what many thinkers had proposed so far, Hegel places content as the fundament of their articulation, albeit in a strict and intrinsic relationship with form. This is due to a logical aspect that permeates the Aesthetics and goes back to the first volume of the Encyclopedia of Philosophical Sciences, resulting in a historical understanding of the content and its adequate external manifestation as form. As a consequence of the articulation of form and content based on the history of spirit, Hegel not only provides an understanding of the individual arts and their realization as artworks, but also offers several reflections that can be used to think about art in his posteriority, concerning for example modernism and the avant-garde movements, where the questioning of form becomes its own content, or the novel, a literary genre which can be constituted under infinite forms, in order to express the subjectivity and reflexive nature of the modern spirit.